C-Reactive protein predicts acute myocardial infarction during high-risk noncardiac and vascular surgery - Oscar M. Martins; Vicente F. Fonseca; Ivan Borges; Vaierio Martins; Vera Lucia Portal; Lucia Campos Pellanda (Clinics, 2011)
BACKGROUND: High-sensitivity C-reactive protein predicts cardiovascular events in a wide range of clinical contexts. However, the role of high-sensitivity C-reactive protein as a predictive marker for perioperative acute myocardial infarction during noncardiac surgery is not yet clear. The present study investigated high-sensitivity C-reactive protein levels as predictors of acute myocardial infarction risk in patients undergoing high-risk noncardiac surgery. METHODS: This concurrent cohort study included patients aged >50 years referred for high-risk noncardiac surgery according to American Heart Association/ACC 2002 criteria. Patients with infections were excluded. Electrocardiograms were performed, and biomarkers (Troponin I or T) and/or total creatine phosphokinase and the MB fraction (CPK-T/MB) were evaluated on the first and fourth days after surgery. Patients were followed until discharge. Baseline high-sensitivity C-reactive protein levels were compared between patients with and without acute myocardial infarction. RESULTS: A total of 101 patients undergoing noncardiac surgery, including 33 vascular procedures (17 aortic and 16 peripheral artery revascularizations), were studied. Sixty of the patients were men, and their mean age was 66 years. Baseline levels of high-sensitivity C-reactive protein were higher in the group with perioperative acute myocardial infarction than in the group with non-acute myocardial infarction patients (mean 48.02 vs. 4.50, p = 0.005). All five acute myocardial infarction cases occurred in vascular surgery patients with high CRP levels. CONCLUSIONS: Patients undergoing high-risk noncardiac surgery, especially vascular surgery, and presenting elevated baseline high-sensitivity C-reactive protein levels are at increased risk for perioperative acute myocardial infarction.